Influence of Reinforcement Volumetric Percentage and Aspect Ratio on Additive Manufactured Multi Material Structure in Uniaxial Loading - Arumaikkannu, G. (2016)
Additive Manufactured multi material structures have an attractive combination of mechanical and thermal properties and are being increasingly used in engineering applications. To meet this need, additive manufacturing has shown the possibilities of processing multiple material with complex geometry in part fabrication. As a result, AM opens a new opportunity for designers to create multi material structure that were unfeasible to be manufactured in traditional techniques. And also it has been noticed that some products may require positioning and orientation of secondary material in a specific way to achieve desired functional properties. In this study the randomly oriented multi material were modelled based on parameters such as aspect ratio and volumetric percentage of secondary material/reinforcement and the same was fabricated using polyjet 3D printing technique. Influence of the parameters on behaviour of randomly oriented multi material structure under tensile loading was investigated. Experimentation results confirmed that the reinforcement parameter influences macroscopic behaviour of the multi material structure, which depends on the reinforcement intersecting point and the size of multi material structure. Multi material structure with higher aspect ratio has increased tensile modulus, where as with increase in volumetric percentage of reinforcement the tensile modulus get decreases.